An in vitro comparison of casein phosphopeptide-amorphous calcium phosphate paste, casein phosphopeptide-amorphous calcium phosphate paste with fluoride and casein phosphopeptide-amorphous calcium phosphate varnish on the inhibition of demineralization and promotion of remineralization of enamel - Prachi Jayesh Thakkar; Chandrashekhar M Badakar; Shivayogi M Hugar; Seema Hallikerimath; Punit M Patel; Parin Shah (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2017)
Aim: This study aims to determine and compare the extent of inhibition of demineralization and promotion of remineralization of permanent molar enamel with and without application of three remineralizing agents. Materials and Methods: Forty extracted permanent molars were randomly divided into two groups 1 and 2, longitudinally sectioned into four and divided into subgroups A, B, C, and D. The sections were coated with nail varnish leaving a window of 3 mm × 3 mm. All sections of Group 1 were treated with their respective subgroup-specific agent: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) paste for subgroup A, CPP-amorphous calcium phosphate fluoride (ACPF) paste for subgroup B, CPP-ACPF varnish for subgroup C and subgroup D served as a control. The sections were then subjected to demineralization for 12 days following which lesional depth was measured under the stereomicroscope. All the sections of Group 2 were subjected to demineralization for 12 days, examined for lesional depth, then treated with their respective subgroup specific agents and immersed in artificial saliva for 7 days. The sections were then examined again under the stereomicroscope to measure the lesional depth. Results: CPP-ACPF varnish caused significant inhibition of demineralization. All three agents showed significant remineralization of previously demineralized lesions. However, CPP-ACPF varnish showed the greatest remineralization, followed by CPP-ACPF paste and then CPP-ACP paste. Conclusion: This study shows that CPP-ACPF varnish is effective in preventing demineralization as well as promoting remineralization of enamel. Thus, it can be used as an effective preventive measure for pediatric patients where compliance with the use of tooth mousse may be questionable.